The History of the Discovery of Cytochrome Group Enzymes - Tuychiyeva Dilfuza Siddikjonova,; Shavkat Numonovich Kodirov,; Hakulova Mukaddas Shavkatovna, (American Journal of Biology and Natural Sciences, 2025)
Cytochromes are hemoproteins containing an iron-porphyrin complex that play a key role in electron transfer and redox reactions in cells. They participate in the respiratory and photosynthetic chains, providing the synthesis of adenosine triphosphate (ATP) and other vital processes. The classification of cytochromes is based on their genetic structure and includes more than 57 families, in particular cytochromes P450, which are important for drug metabolism and detoxification. The functions of cytochromes vary depending on their type and localization, including involvement in immune responses and regulation of metabolism. Cytochromes are widely used in biochemistry, pharmacology, and medicine, being the object of study in the development of new drugs and the assessment of their metabolic activity.